Pengaruh Penggunaan Media Audio Visual Terhadap Kemampuan Berbahasa Anak Usia 5-6 Tahun di Paud Ronatama - Mely Sulastri Simamora; Hisardo Sitorus (Khirani: Jurnal Pendidikan Anak Usia Dini, 2024)
Simamora, Mely. 2023. "The Effect of Using Audio Visual Media on the Language Ability of Children Aged 5-6 Years in PAUD Ronatama." Thesis: Tarutung State Christian Institute PK-AUD Study Program. The aim of this research is to determine the effect of using audio-visual media on language skills in children aged 5-6 years in Ronatama Early Childhood Education, Doloksanggul District. The method used in this research is a quantitative research method with a pre-experimental design type of research in the form of "One Shot Case Study". The population is all children aged 5-6 years in PAUD Ronatama, Doloksanggul subdistrict, totaling 20 children. Data was collected using a positive closed questionnaire with 10 items for variable Lesson 2023/2024: 1) Test the analysis requirements: a) test a positive relationship, obtain a value of rxy = 0.668 > rtable= 0.444, so it is known that there is a positive relationship between variable X and variable Y. b) Test a significant relationship, obtain a value of tcount = 3.811 > ttable 2.101, thus there is a significant relationship between variable 9.89"+0.72X. Thus Ha is accepted and H0 is rejected.